The training of portuguese teachers in basic education in portugal: confluences and intersections in supervised practice - Custódio, Pedro Balaus (Revista Hipótese, 2022)
In Portugal, over the last few decades, teacher training models have had a special emphasis on the construction of teachers' qualifications. Our aim is to describe how the current model for the training of Portuguese teachers in Basic Education is structured and also how the theoretical aspects in the field of supervised teaching practice converge. Based on the curriculum of one of the courses taught at the Polytechnic of Coimbra and the current internship model, we will revisit this example of training Portuguese teachers for this teaching cycle.
Keywords: Teacher training; Basic Education in Portugal; Portuguese teaching